In Honor of Professor Zhifang Chai - Wang, Dongqi; Zhang, Zhiyong (Molecules (Basel, Switzerland), 2024)
We are delighted to dedicate this Special Issue to a leading figure in actinoid chemistry, Prof [...].We are delighted to dedicate this Special Issue to a leading figure in actinoid chemistry, Prof [...].